Relationship between cephalic biotype and severity of periodontal disease in the canine - Paz M., Ricardo (2012)
The aim of the study was to determine the association between cephalic biotype and severity of periodontal disease in dogs in a pet clinic in Lima between September 2008 and March 2009. Forty five patients’ heads older than one year were classified by the Cephalic Index in brachycephalic and not brachycephalic (mesaticephalic and dolicocephalic), and then, the teeth was evaluated through the Veterinary Periodontal Index. The result showed that 57.8% of animals had periodontal disease, where 81.2% were brachycephalic dogs and 44.8% were not brachycephalic (p<0.05). There was statistical association between missing teeth and presence of periodontal disease. The most affected teeth were premolars.